Structure-property relationships of a biopolymer network: The eggshell membrane - Torres F.G. (2010)
The eggshell membrane (ESM) is a biopolymer network that may have potential applications in biomedicine, but it also may reveal important details regarding the behaviour of biopolymer networks. In this paper, we have studied the mechanical and morphological properties of the ESM in order to reveal important structure-property relationships. Light optical microscopy and atomic force microscopy were used to assess the morphology of the ESM. The mechanical properties of membranes and individual fibres were studied by means of tensile tests and nanoindentation tests, respectively. The mechanical behaviour of ESM networks in different environmental conditions showed a non-linear and a linear regime. As for elastomers and other biopolymer systems, the non-linear regime was modelled by the Mooney-Rivlin relation. The Young's modulus in the linear regime of the network was related to the Young's modulus of the individual fibres using Gibson and Ashby analysis for cellular solids. The results of morphological characterization were used to relate the properties of individual fibres to the properties of the whole networks. This enabled us to predict the macroscopical properties of the network based on the properties of the individual fibres. It was found that the ESM networks behaved as both Mooney-Rivlin and Hookean materials in different environmental conditions. This study helps elucidate the properties of the biopolymer networks found in nature and describes important mechanical properties for the use of the ESM as a biomaterial.